2020
DOI: 10.3390/jcm9113734
|View full text |Cite
|
Sign up to set email alerts
|

Is the Oxidative Stress in Obstructive Sleep Apnea Associated with Cardiovascular Complications?—Systematic Review

Abstract: Obstructive sleep apnea (OSA) is a prevalent, underdiagnosed disease and is considered an independent risk factor for cardiovascular disease. The exact mechanism of cardiovascular complications (CVC) development as a complication of OSA is not entirely understood. Oxidative stress is suspected to be the essential factor in initiating various comorbidities in OSA. Biomarkers of nonenzymatic lipid and protein peroxidation, DNA repair and antioxidant capabilities measured in serum, plasma and urine are frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
13
1
Order By: Relevance
“…Advanced glycation end product (AGE) accumulation along with increased protein kinase C, polyol, and hexosamine pathway activity could lead to the overexpression of reactive oxygen species (ROS) and pro-inflammatory cytokines, all of which have a role in diabetic complications [70,[104][105][106][107][108]. Indeed, some papers suggest an association between OSA and markedly increased intracellular ROS concentrations [including mainly superoxide ion (O -), nitric oxide (NO), and hydrogen peroxide (H 2 O 2 )], which, by overwhelming antioxidant capacity, chemically modify lipidic, protidic, and DNA macromolecules [109][110][111][112][113][114].…”
Section: Pathophysiology Of T2dm Micromacrovascular Complications In Patients With Osamentioning
confidence: 99%
“…Advanced glycation end product (AGE) accumulation along with increased protein kinase C, polyol, and hexosamine pathway activity could lead to the overexpression of reactive oxygen species (ROS) and pro-inflammatory cytokines, all of which have a role in diabetic complications [70,[104][105][106][107][108]. Indeed, some papers suggest an association between OSA and markedly increased intracellular ROS concentrations [including mainly superoxide ion (O -), nitric oxide (NO), and hydrogen peroxide (H 2 O 2 )], which, by overwhelming antioxidant capacity, chemically modify lipidic, protidic, and DNA macromolecules [109][110][111][112][113][114].…”
Section: Pathophysiology Of T2dm Micromacrovascular Complications In Patients With Osamentioning
confidence: 99%
“…Additionally, several authors have reported that continuous positive airway pressure therapy (nCPAP) not only reduces intermittent hypoxia but also attenuates lipid peroxidation in OSA patients [14,57]. A recent systematic review reported the presence of high concentrations of biomarkers of oxidative stress in OSA and a correlation between these biomarkers and the severity of the disease [58]. MDA is the most abundant aldehyde generated during the lipid peroxidation process and represents one of the most investigated markers of oxidative stress status in different lung diseases [12,59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these patients also suffered from concomitant diseases, i.e., hypertension, diabetes, and arrhythmia, which are related to destroying the oxidative/antioxidative balance. Our recently published systematic review showed the extent of oxidative stress associated with OSAS; however, with no clear difference between OSAS patients with and without cardiovascular complications [ 31 ]. Moreover, we found studies reported no differences in levels of oxidative stress biomarkers between groups of OSAS patients with biometrical differences (age, BMI, AHI) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our recently published systematic review showed the extent of oxidative stress associated with OSAS; however, with no clear difference between OSAS patients with and without cardiovascular complications [ 31 ]. Moreover, we found studies reported no differences in levels of oxidative stress biomarkers between groups of OSAS patients with biometrical differences (age, BMI, AHI) [ 31 ]. When this was taken into consideration, in order to better explain the relationship between oxidative stress and the severity of obstructive sleep apnea, we identified the need to investigate abnormities in the oxidative/reductive status in tissues gathered from OSAS patients during sleep surgeries, i.e., palatoplasty and palatopharyngoplasty.…”
Section: Discussionmentioning
confidence: 99%